2021
DOI: 10.3390/agriculture11040285
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Effects of Calcium Sprays on Yield and Grain Nutritional Composition of Maize (Zea mays L.) Cultivars under Drought Stress

Abstract: Drought stress is seriously affecting maize production. To investigate the influence of calcium (Ca) foliar application on maize production and chemical composition of grains under drought stress, two experiments were carried out at Cairo University Research Station, Giza, Egypt, during the summer seasons of 2018 and 2019. The experimental design was split-split plot design with a completely randomized blocks arrangement with three replications. Water regimes were assigned to the main plots [100 (control), 75,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 77 publications
3
10
0
2
Order By: Relevance
“…Therefore, we expected PA supplementation to induce a good CH transport, enhancing the kernel set and the final yield. As a result, WD reduced the CH content compared to the WW conditions in untreated plants, as previously observed by Hussain et al (2020) and Abbas et al (2021) . However, opposite results were also published.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Therefore, we expected PA supplementation to induce a good CH transport, enhancing the kernel set and the final yield. As a result, WD reduced the CH content compared to the WW conditions in untreated plants, as previously observed by Hussain et al (2020) and Abbas et al (2021) . However, opposite results were also published.…”
Section: Discussionsupporting
confidence: 83%
“…Low water availability increased the protein content in the flour, as described by Lu et al (2015) ; Barutcular et al (2016) , and Abbas et al (2021) . However, other studies showed no alterations in the protein content by the water restriction ( Hussain et al, 2020 ).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…It was indicated that the foliar application of Ca 2+ caused effective shoot growth and distributed fairly more sucrose to the beetroots in response to drought stress (Hosseini et al, 2019). Besides, foliar application of calcium, increase considerably maize yield and ionic contents of grains including N, P, K and Fe which decreased water stress due to the decreased transpiration rate, declined active transport and depressed membrane permeability that results in restriction of nutrient uptake under water deficiency conditions (Abbas et al, 2021). Foliar application of calcium is expected to rise intracellular Ca levels that can stimulate Ca dependent protein kinases and leads to regulating the expression levels of stressresponsive genes through phosphorylate or dephosphorylate specific transcription factors (Reddy et al, 2011).…”
Section: Role Of Cations In Drought Stressmentioning
confidence: 99%
“…Water deficiency is the main challenge for cotton growth and productivity, especially in arid and semiarid areas worldwide. Drought stress is expected to be more repeated and acute due to global climate change, with harmful impacts on the world's crop production (Abbas et al, 2021). Cotton water requirement is 3000 to 3500m 3 /f during the fall season to obtain a normal yield.…”
Section: Introductionmentioning
confidence: 99%